FAKTOR SOSIODEMOGRAFI, PENGETAHUAN DAN PERILAKU MAKAN ANAK TERHADAP KEMAMPUAN KOGNITIF DI DAERAH ENDEMIS GANGGUAN AKIBAT KEKURANGAN YODIUM - , METTY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: IDD is a nutrition problem of school children in Indonesia, including at Subdistrict of Cangkringan, Province of Yogyakarta Special Territory. The prevalence for having goitre of the population at Subdistrict of Cangkringan is 39.5%